Impact of family DOTS on tuberculosis treatment outcomes and associated factors in tribal and hard to reach areas in the state of Chhattisgarh: an implementation research - Kerketta, Fidius; Sinha, Ashish; Tripathi, Narayan; Borkar, Arti; Gupta, Shashank; Nahak, Anupam (International Journal Of Community Medicine And Public Health, 2021)
Background: Tuberculosis (TB) remains a worldwide healthcare problem and it is one of the major public health concerns in India including Chhattisgarh state. National tuberculosis elimination program (NTEP) has adopted direct observed treatment (DOTS) strategy for elimination of TB. Due to inaccessibility and difficult to reach areas in the tribal areas, monitoring of treatment adherence and treatment completion remains a challenge leading to poor treatment outcomes among TB cases. This implementation research was aimed to assess the impact of family DOTS on the TB treatment outcomes in a tribal district of Chhattisgarh. Methods: A prospective cohort study of all new smear positive sputum, new smear negative sputum and extra-pulmonary TB patients who were newly diagnosed and registered for treatment under the revised national tuberculosis control programme (RNTCP) in hard to reach district was implemented between November 2016 to January 2018. They were followed till the completion of the treatment. Results: Total 305 tuberculosis new patients (218 intervention and 87 in comparison blocks) were registered for treatment at health facilities in study area. The treatment success rate in the comparison group was better (72.41%) compared to the intervention group (68.35%). Similar results have been observed in terms of non-adherence to treatment and death rate. Sputum conversion rate was observed to have 94% in intervention group in comparison to 95% comparison group. Conclusions: Family DOTS may not be effective unless there is involvement from the RNTCP by regular monitoring and follow up.